Модель устройчивого развития в подсистеме ЖКХ «собственник-управляющая компания» - Ясеновский, Э. П.; Наумейко, И. В.; Сова, А. В. (ХНУРЭ, 2016)
Within the limits of the general model the dynamics of mathematical models for exposition of competitive processes was investigated. In engineering systems with several sources and a customer the conditions of steady growth and elimination the conditions of chaos were detected. "Steady growth" is a rather new concept and does not assume sufficing to classical definitions of stability by Lyapunov.
Keywords: подсистема ЖКХ; устройчивое развитие